Increasing Jatam Kroya’s Agricultural Production by Creating “Boosters” from the Environment - Wakhudin, Wakhudin; Wijanarko, Beny R; Purbomartono, Cahyono (Edumedia Solution, 2025)
This community service (IbM) aims to increase agricultural production in the community that is part of the Muhammadiyah Farmers Association (Jatam) in Kroya District, Cilacap Regency, Central Java by making